Longitudinal Relationships of Physical Activity, Sedentary Time, Cardiorespiratory Fitness, and Muscular Fitness with Body Fatness in Preschoolers - Kirkke Reisberg; Eva-Maria Riso; Liina Animägi; Jaak Jürimäe (MDPI AG, 2024)
There is still insufficient knowledge about the potential benefits of physical activity and fitness or the adverse impact of sedentary behaviours on body composition at preschool age. Therefore, we aimed to study the relationships of moderate-to-vigorous physical activity (MVPA), sedentary time (ST), cardiorespiratory fitness (CRF), and muscular fitness (MF) with body fat percentage (BF%) in boys and girls. Participants were investigated twice: in the final year of kindergarten, when the boys' median age was 7 years and the girls' median age was 6 years (p = 0.240), and again in the first grade of school. MVPA and ST were measured with an accelerometer, BF% was derived from skinfold thicknesses, CRF was measured with a 20 m shuttle run test, and MF was represented by the mean z-scores from standing long jump and relative upper-limb strength. In girls, higher ST (β = 0.587, p = 0.021) and lower MF (β = −0.231, p = 0.009) at preschool age were related to higher BF% in the first grade of school after adjustment for confounders. MVPA and CRF in preschool children were unrelated to BF% in school among boys and girls. In conclusion, sitting less and having greater muscular fitness at preschool age appear to be beneficial for lower body fatness in the first grade among girls, but not in boys. MVPA and CRF at preschool age are unrelated to body fatness at school age in boys and girls. Our results indicate that girls may especially benefit from decreasing sedentary behaviours and increasing upper- and lower-limb muscular strength at preschool age for a healthy weight profile in the first grade of school.